Die Berücksichtigung von Hilfsmitteln bei der Verletztenrente - Vogt, Mona Marie, (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The thesis examines the eligibility for considerations of aids for the injury pension of the statutory acci-dent insurance, in particular with regard to the concept of the term MdE, the tasks of the injury pension and various principles of the statutory accident insurance as well as Art. 3 GG. Furthermore, the thesis deals with the question which aids can be taken into account and who should be the decision-maker for the consideration. The latter is closely related to the discussion on the constitutionality of the MdE tab-les.